Development of Guided Discovery-Based e-Module on Colligative Properties to Improve Higher Order Thinking Skills of High School Students - Nofrianto, Nofrianto; Latisma, Latisma; Kurniawati, Desy; Putra, Ananda (Jurnal Pendidikan MIPA, 2022)
The current condition of the Covid-19 pandemic is very influential on the learning process in schools so that a teaching material is needed that can increase the activity of students. This study aims to develop an e-module of colligative properties of solutions based on Guided Discovery Learning to improve Higher Order Thinking Skills (HOTS), as well as determine the level of validity, practicality and effectiveness of the developed e-module. This research and development uses the Plomp model which consists of 3 stages. The assessment instruments used are observation sheets, questionnaires, and learning outcomes tests. The e-Module was validated by six expert validators and tested on six students and 36 students at SMAN 14 Padang. The validity results of the e-module obtained an average value of Aiken's V of 0.84 with a very valid category. The results of e-module practicality by teachers and students obtained an average score of 0.90 and 0.88 with a very practical category. The results of the e-module learning effectiveness test obtained an average N-gain value of 0.691 with a moderate category Keywords: e-module, guided discovery learning, higher order thinking skills, Plomp development model, colligative properties of solutions. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1038-1046